INNOVATIVE MEASURES OF PROVIDING YOUTH EMPLOYMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, it is stated that the state's innovative policy of ensuring youth employment in Uzbekistan has shown its positive results in social life over the years.